Five-year results from a phase 2 study of oral fingolimod in relapsing multiple sclerosis. (June 2014) - Izquierdo, G; O'Connor, P; Montalban, X; von Rosenstiel, P; Cremer, M; de Vera, A; Sfikas, N; Francis, G; Radue, EW; Kappos, L
We present here results at 60 months (M), from the extension component of a phase 2, randomized, placebo-controlled, double-blind, six-month study evaluating oral fingolimod (1.25 mg or 5 mg daily) in relapsing multiple sclerosis. Placebo patients from the core study were re-randomized to fingolimod 1.25 mg or 5 mg in the extension. All patients received 1.25 mg fingolimod after the M24 visit. A total of 140/281 (49.8%) patients completed M60. Fingolimod treatment was associated with a low annualized relapse rate (0.2 relapses/ year), low MRI activity, and a modest rate of disability progression in those treated for five years. No new safety issues were reported.